CURRICULUM MANAGEMENT OF IDAD MURABBI PROGRAM IN IMPROVING THE QUALITY OF PROSPECTIVE EDUCATORS: A CASE STUDY AT STIPI MAGHFIRAH - El Hanif, Zubair Qudsi; Sastra, Ahmad; Sa'diyah, Maemunah; Azhar, Rayhan; M. Nur, Firman (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Teacher quality is factor key quality Islamic education is required balance competence academic and character . Research This analyze management I'dad Murabbi Program curriculum at STIPI Maghfirah , cadre development model intensive " Warrior Teacher ". Research objectives is describe implementation management curriculum , its contribution to quality murabbi on MILBoS, as well as its development strategy . Use method qualitative descriptive , data collected through interviews , observations , and documentation , then analyzed with the interactive model of Miles, Huberman, and Saldaña. Findings show management curriculum implemented through planning based standard six competence murabbi ( mindset , spiritual, social , practical , leadership , and managerial ). Organizing done with structure authority clear , while implementation blend formal learning with approach living curriculum in the dormitory. Evaluation implemented in a way daily , weekly , and incidental For ensure accountability . This program in a way significant increase spiritual maturity , skills pedagogy , and readiness adaptation prospective teachers in the field . In theoretical , research This contribute to the management model curriculum Islamic education that integrates aspect cognitive and affective in dormitory ecosystem